ANALISIS BERPIKIR KREATIF SISWA SMP DALAM PEMBELAJARAN BERDIFERENSIASI DENGAN MEMPERHATIKAN GAYA BELAJAR MELALUI MODEL PJBL PADA MATERI KUBUS DAN BALOK - Nahmudiyah, Sukses Agustin; Faridah, Luluk; Aini, Khafidhoh Nurul (INSPIRAMATIKA, 2025)
The level. of creative thinking ability among students in Indonesia is still relatively low. One solution to overcome this is to implement differentiated learning based on learning styles through the PjBL model. This study was conducted to analyze how students' creative thinking abilities vary according to their learning styles. This research employs a qualitative approach, with the research instruments including a questionnaire on learning styles, a creativity test, and an interview guide as supporting tools. This study identified that: (1) Visual learners met the fluency indicators and fell into the creative category; (2) Auditory learners met the fluency and detail indicators and fell into the creative category; (3) Kinesthetic learners met the fluency and flexibility indicators and had a high level of creativity.